1998
DOI: 10.5006/1.3284894
|View full text |Cite
|
Sign up to set email alerts
|

Telluric Currents: A Meeting of Theory and Observation

Abstract: Pipe-to-soil (P/S) potential variations resulting from telluric currents have been observed on pipelines in many locations.However, it has never been clear which parts of a pipeline will experience the worst effects. Two studies were conducted to answer this question. Distributed-source transmission line (DSTL) theory was applied to the problem of modeling geomagnetic induction in pipelines. This theory predicted that the largest P/S potential variations would occur at the ends of the pipeline. The theory also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
22
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 4 publications
7
22
0
Order By: Relevance
“…[17] The trends in the effective impedance curves are consistent with the E/B ratio given by Campbell [1986] and Pirjola [1982] and the 180°phase difference is consistent with PSP signals on either side of a pipeline insulating joint [Boteler and Seager, 1998]. The order of magnitude difference between the effective impedance curves for different PSP sites on a pipeline may be due to the distance between grounding points, or pipeline orientation with respect to the source fields.…”
Section: Discussion and Modelingsupporting
confidence: 63%
See 4 more Smart Citations
“…[17] The trends in the effective impedance curves are consistent with the E/B ratio given by Campbell [1986] and Pirjola [1982] and the 180°phase difference is consistent with PSP signals on either side of a pipeline insulating joint [Boteler and Seager, 1998]. The order of magnitude difference between the effective impedance curves for different PSP sites on a pipeline may be due to the distance between grounding points, or pipeline orientation with respect to the source fields.…”
Section: Discussion and Modelingsupporting
confidence: 63%
“…Similar studies have also been conducted in the Tierra del Fuego region of South America [Osella et al, 1998;Osella and Favetto, 2000]. Large GICs have been correlated with the largest rate of change of the geomagnetic field [Viljanen, 1997;Viljanen et al, 1999;Trichtchenko and Boteler, 2004] and simulations of PSPs on Canadian and Scandinavian pipelines have also been conducted [Boteler and Seager, 1998;Pulkkinen et al, 2001b;Trichtchenko and Boteler, 2002;Fernberg et al, 2007]. GIC signals observed on low-latitude pipelines [Martin, 1993;Waters et al, 2006] are likely to have different ionospheric source fields to those observed on high-latitude pipelines and provide additional spectral information for comparison with model predictions.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations